2015
DOI: 10.3310/hta19580
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic point-of-care testing to assist with the diagnosis, management and monitoring of haemostasis: a systematic review and cost-effectiveness analysis

Abstract: BackgroundPatients with substantive bleeding usually require transfusion and/or (re-)operation. Red blood cell (RBC) transfusion is independently associated with a greater risk of infection, morbidity, increased hospital stay and mortality. ROTEM (ROTEM®Delta, TEM International GmbH, Munich, Germany;www.rotem.de), TEG (TEG®5000 analyser, Haemonetics Corporation, Niles, IL, USA;www.haemonetics.com) and Sonoclot (Sonoclot®coagulation and platelet function analyser, Sienco Inc., Arvada, CO) are point-of-care visc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
250
1
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(268 citation statements)
references
References 114 publications
8
250
1
9
Order By: Relevance
“…The trial by Karkouti and colleagues 7 also failed to demonstrate any difference in overall complication rates; although again the exact complications and their frequencies were not specified. Overall, the results of this trial mirrored the findings of the 2016 Cochrane review; 33 notably, that the use of viscoelastic testing reduced transfusion, but had no benefit with respect to objective clinically important end points. This is at odds with the findings of the systematic review conducted by Whiting and colleagues, 33 who concluded that viscoelastic testing was likely to be cost-effective.…”
Section: Strengths and Limitationssupporting
confidence: 61%
See 2 more Smart Citations
“…The trial by Karkouti and colleagues 7 also failed to demonstrate any difference in overall complication rates; although again the exact complications and their frequencies were not specified. Overall, the results of this trial mirrored the findings of the 2016 Cochrane review; 33 notably, that the use of viscoelastic testing reduced transfusion, but had no benefit with respect to objective clinically important end points. This is at odds with the findings of the systematic review conducted by Whiting and colleagues, 33 who concluded that viscoelastic testing was likely to be cost-effective.…”
Section: Strengths and Limitationssupporting
confidence: 61%
“…Overall, the results of this trial mirrored the findings of the 2016 Cochrane review; 33 notably, that the use of viscoelastic testing reduced transfusion, but had no benefit with respect to objective clinically important end points. This is at odds with the findings of the systematic review conducted by Whiting and colleagues, 33 who concluded that viscoelastic testing was likely to be cost-effective. Their analysis directly informed current National Health Service NICE Guidelines, which recommend routine use of viscoelastic testing in cardiac surgery.…”
Section: Strengths and Limitationssupporting
confidence: 61%
See 1 more Smart Citation
“…In trauma patients with TIC, evidence exists that viscoelastic tests supersede CCTs in delineating the process of the clotting cascade and therefore are useful in guiding blood products transfusion [7]. Recent guidelines on the management of TIC encourages a treatment strategy focused on goal directed resuscitation with more restriction in the use of intravenous fluids during initial resuscitation [10].…”
Section: Introductionmentioning
confidence: 99%
“…65 Evidence also supports the cost-effectiveness of VHAs compared with CCTs. 66 Device-specific limitations may influence the preference of one VHA platform over the other. While the standard ROTEM device is automated and capable of analyzing 4 samples simultaneously, the TEG device is limited to 2 samples at a time.…”
mentioning
confidence: 99%